Measuring biodiversity and sustainable management in forests and agricultural landscapes - Dudley, N.; Baldock, D.; Nasi, Robert; Stolton, S. (2005)
Most of the world’s biodiversity will continue to exist outside protected areas and there are also managed lands within many protected areas. In the assessment of millennium targets, there is therefore a need for indicators to measure biodiversity and suitability of habitats for biodiversity both across the whole landscape/seascape and in specific managed habitats. The two predominant land uses in many inhabited areas are forestry and agriculture and these are examined. Many national level criteria and indicator systems already exist that attempt to assess biodiversity in forests and the impacts of forest management, but there is generally less experience in measuring these values in agricultural landscapes. Existing systems are reviewed, both for their usefulness in providing indicators and to assess the extent to which they have been applied. This preliminary gap analysis is used in the development of a set of indicators suitable for measuring progress towards the conservation of biodiversity in managed forests and agriculture. The paper concludes with a draft set of indicators for discussion, with suggestions including proportion of land under sustainable management, amount of produce from such land, area of natural or high quality semi-natural land within landscapes under sustainable management and key indicator species.